Metabolic enzyme activities of abyssal and hadal fishes: pressure effects and a re-evaluation of depth-related changes. (July 2017) - Gerringer, M.E.; Drazen, J.C.; Yancey, P.H.
Abstract: Metabolic enzyme activities of muscle tissue have been useful and widely-applied indicators of whole animal metabolic capacity, particularly in inaccessible systems such as the deep sea. Previous studies have been conducted at atmospheric pressure, regardless of organism habitat depth. However, maximum reaction rates of some of these enzymes are pressure dependent, complicating the use of metabolic enzyme activities as proxies of metabolic rates. Here, we show pressure-related rate changes in lactate and malate dehydrogenase (LDH, MDH) and pyruvate kinase (PK) in six fish species (2 hadal, 2 abyssal, 2 shallow). LDH maximal reaction rates decreased with pressure for the two shallow species, but, in contrast to previous findings, it increased for the four deep species, suggesting evolutionary changes in LDH reaction volumes. MDH maximal reaction rates increased with pressure in all species (up to 51±10% at 60 MPa), including the tide pool snailfish, Liparis florae (activity increase at 60 MPa 44±9%), suggesting an inherent negative volume change of the reaction. PK was inhibited by pressure in all species tested, including the hadal liparids (up to 34±3% at 60 MPa), suggesting a positive volume change during the reaction. The addition of 400 mM TMAO counteracted this inhibition at both 0.5 and 2.0 mM ADP concentrations for the hadal liparid, Notoliparis kermadecensis . We revisit depth-related trends in metabolic enzyme activities according to these pressure-related rate changes and new data from seven abyssal and hadal species from the Kermadec and Mariana trenches. Results show that, with abyssal and hadal species, pressure-related rate changes are another variable to be considered in the use of enzyme activities as proxies for metabolic rate, in addition to factors such as temperature and body mass. Intraspecific increases in tricarboxylic acid cycle enzymes with depth of capture, independent of body mass, in two hadal snailfishes suggest improved nutritional condition for individuals deeper in the hadal zone, likely related to food availability. These new data inform the discussion of factors controlling metabolism in the deep sea, including the visual interactions hypothesis and extend published trends to the planet's deepest-living fishes. Highlights: Metabolic enzyme activities from abyssal and hadal fishes. Pressure-activation of lactate dehydrogenase in abyssal and hadal fishes. Pressure-activation of malate dehydrogenase in all species tested. Pressure-inhibition of pyruvate kinase counteracted by TMAO in hadal fish. Pressure effects should be considered in studies of metabolic rate at abyssal and hadal depths.